Preliminary observations of rat control in oil palm plantations using jelly baits - Chee, K.H. (2013)
A watery jelly bait made in the estate using a water retaining polymer and a slow acting anticoagulation rodenticide was more effective than the conventional wax cube bait in controlling rat damage in oil palm plantations during the long dry season. Jelly rat bait is relatively cheap and it kills the rat with a lower dosage of rodenticide